Small-angle scattering to reveal the colloidal nature of halide perovskite precursor solutions. Issue 23 (1st June 2021) - Flatken, Marion A.; Hoell, Armin; Wendt, Robert; Härk, Eneli; Dallmann, André; Prause, Albert; Pascual, Jorge; Unger, Eva; Abate, Antonio
Abstract : We present small-angle scattering as a nanostructural technique to characterize the colloidal nature of perovskite precursor dispersions. The existence of a dynamic colloidal network has been proven to influence the initial stages of crystallization. Abstract : Halide perovskites are crystalline semiconductors gaining increasing attention as low-cost, high-performance materials for optoelectronics. Their processing from solution at low temperatures is compatible with rapid manufacturing of thin-film devices, including solar cells and light-emitting diodes. Therefore, understanding the coordination chemistry in metal halide perovskite precursor solutions would allow controlling the crystallization of thin films, their material properties and device performance. Here, we present a direct nanostructural technique to characterize the colloidal structure of perovskites in precursor solutions. Small-angle scattering is particularly adept for measuring nanoparticles in solution. Applying this technique to perovskite precursor solutions, we can study their colloidal properties. We show that not only do the colloids themselves matter, but also we can reveal their strong interactions in the early stages of crystallization. In particular, we focus on the prearrangement of particles into cluster-like formations. As an example, we present the concentration dependence, which is additionally supported using 207 Pb NMR.